3D correction over 2 years with anterior vertebral body growth modulation: A finite element analysis of screw positioning, cable tensioning and postoperative functional activities. (January 2018) - Cobetto, Nikita; Parent, Stefan; Aubin, Carl-Eric
Abstract: Background: Anterior vertebral body growth modulation is a fusionless instrumentation to correct scoliosis using growth modulation. The objective was to biomechanically assess effects of cable tensioning, screw positioning and post-operative position on tridimensional correction. Methods: The design of experiments included two variables: cable tensioning (150/200 N) and screw positioning (lateral/anterior/triangulated), computationally tested on 10 scoliotic cases using a personalized finite element model to simulate spinal instrumentation, and 2 years growth modulation with the device. Dependent variables were: computed Cobb angles, kyphosis, lordosis, axial rotation and stresses exerted on growth plates. Supine functional post-operative position was simulated in addition to the reference standing position to evaluate corresponding growth plate's stresses. Findings: Simulated cable tensioning and screw positioning had a significant impact on immediate and after 2 years Cobb angle (between 5°–11°, p < 0.01). Anterior screw positioning significantly increased kyphosis after 2 years (6°–8°, p = 0.02). Triangulated screw positioning did not significantly impact axial rotation but significantly reduced kyphosis (8°–10°, p = 0.001). Growth plates' stresses were increased by 23% on the curve's convex side with cable tensioning, while screw positioning rather affected anterior/posterior distributions. Supine position significantly affected stress distributions on the apical vertebra compared to standing position (respectively 72% of compressive stresses on convex side vs 55%). Interpretation: This comparative numerical study showed the biomechanical possibility to adjust the fusionless instrumentation parameters to improve correction in frontal and sagittal planes, but not in the transverse plane. The convex side stresses increase in the supine position may suggest that growth modulation could be accentuated during nighttime. Highlights: Vertebral body tethers can be adjusted to correct coronal and sagittal planes. Axial rotation was not significantly corrected. Supine position affected spinal correction and stress distribution. Growth modulation from the tether could be accentuated during nighttime. Finite element modeling helps to design vertebral body tethering.